A fadD mutant of Vibrio cholerae Is Impaired in the Production of Virulence Factors and Membrane Localization of the Virulence Regulatory Protein TcpP - Ray, Sreejana (American Society for Microbiology (ASM), 2011)
In the enteric pathogen Vibrio cholerae, expression of the major virulence factors is controlled by the hierarchical expression of several regulatory proteins comprising the ToxR regulon. In this study, we demonstrate that disruption of the fadD gene encoding a long-chain fatty acyl coenzyme A ligase has marked effects on expression of the ToxR virulence regulon, motility, and in vivo lethality of V. cholerae. In the V. cholerae fadD mutant, expression of the major virulence genes ctxAB and tcpA, encoding cholera toxin (CT), and the major subunit of the toxin-coregulated pilus (TCP) was drastically repressed and a growth-phase-dependent reduction in the expression of toxT, encoding the transcriptional activator of ctxAB and tcpA, was observed. Expression of toxT from an inducible promoter completely restored CT to wild-type levels in the V. cholerae fadD mutant, suggesting that FadD probably acts upstream of toxT expression. Expression of toxT is activated by the synergistic effect of two transcriptional regulators, TcpP and ToxR. Reverse transcription-PCR and Western blot analysis indicated that although gene expression and production of both TcpP and ToxR are unaffected in the fadD mutant strain, membrane localization of TcpP, but not ToxR, is severely impaired in the fadD mutant strain from the mid-logarithmic phase of growth. Since the decrease in toxT expression occurred concomitantly with the reduction in membrane localization of TcpP, a direct correlation between the defect in membrane localization of TcpP and reduced toxT expression in the fadD mutant strain is suggested.